A Study of 21st-Century Skills Among Senior High School Students in the Context of Project-Based Renewable Energy Learning in South Sumatra Province - Ketang Wiyono; Melly Ariska; Evelina Astra Patriot; Frendi Ihwan Syamsudin; Nor Farahwahidah; Tyse Ramadhona; Senandung Senja Citra Maharani; Laura Insan Kencana; Dea Rizky Oktavia (Postgraduate, University of Mataram, 2026)
The rapid development of science and technology demands that students master essential 21st-century skills, particularly the 4Cs: critical thinking, creativity, collaboration, and communication. This study aims to map senior high school students’ mastery of 4C skills in Renewable Energy learning and to examine differences across the four components. A quantitative descriptive design was applied involving four schools selected through cluster sampling, with each school representing one 4C component. Research instruments consisted of validated and reliable tests and Likert-scale questionnaires. Data were analyzed using descriptive statistics to categorize skill levels and the Kolmogorov–Smirnov test to assess normality. As most data were not normally distributed, the Kruskal–Wallis test was employed to analyze differences among the skills. The results reveal significant variation in students’ 4C performance. Critical thinking and collaboration were categorized as high, while creativity and communication showed more diverse distributions. The Kruskal–Wallis test produced an Asymp. Sig value of < 0.05, indicating significant differences among the four skill domains. These findings suggest that 4C skill development is uneven and influenced by learning experiences and instructional strategies. Therefore, systematic mapping of 4C skills is crucial for curriculum improvement and the design of targeted instructional interventions.